Simulation of a GPON-Based Fiber-To-The-Home Access Network - Manokaran, Mirrwin; Cholan, Noran Azizan (Evolution in Electrical and Electronic Engineering, 2024)
As optical fiber communication technology advances, there is a growing demand for increased transmission speeds, extended transmission distances, and wider transmission bandwidths. Telecommunication companies are actively addressing these requirements through continuous monitoring and evaluation of their fiber optic access network systems. Research in this field seeks to explore the design and analysis of these systems. This study introduces a passive optical network architecture designed to fulfill the demands of the widely-used Gigabit Passive Optical Network (GPON) system. Using ‘OptiSystem’ software, this design is simulated with consideration for real-world system parameters. The simulation assesses the GPON design's compatibility with newer NG-PON1 and NG-PON2 systems and evaluates network performance by minimizing bit errors and enhancing the network quality factor. The model relies on data sourced from published articles about existing networks, with a primary focus on testing GPON network performance using ‘Optisystem’ optical network software.